P108 Closing the audit cycle after updated proctitis guidelines: are we treating too much or too little?. (8th June 2017) - Gostick, Benjamin; Bayley, Jake; Singh, Selena
Abstract : Introduction: There are currently no national guidelines for the management of proctitis. Given the rising rates of STI's, we modified our current guidelines and audited the outcomes pre and post-guideline change. Methods: Retrospective case note analysis was performed on all patients who were coded as proctitis (C4NR) before and after the guidelines were modified. We collected information on demographics, HIV status, symptoms, investigations, treatment and outcomes. Results: We returned 64 patient records over 67 visits, 39 pre and 25 post-guideline changes. 31% (20/64) were HIV positive. Commonest presentations were PR bleeding (49%), rectal discharge (44%) and diarrhoea (28%). 55/64 (88%) had rectal microscopy, with 42/55 (76%) having pus cells present; of these 3/42 (7%) had GC seen on microscopy. There were very low levels of urethral STI rates (just one case of each), but high rates of rectal GC and CT (24% and 13% respectively). LGV was positive in 5% (3/54) and rectal HSV was found in 25% (10/40). There were more HSV swabs sent before versus after guideline modification (19/40 versus 21/27, p=0.01). Discussion: The audit has shown that the addition of HSV swabs and treatment into the guideline had a positive effect, with more cases of HSV proctitis being diagnosed and treated. Our guidelines were also modified to include LGV treatment, but given the low prevalence this may be rationalised. On-going work around coding is also planned as many were coded as proctitis without rectal microscopy.